At turde skabe momentum - kompetencebehov i et hybridt og internationalt bibliotekslandskab - Elbeshausen, Hans; Delica, Kristian Nagel (Nordisk Tidsskrift for Informationsvidenskab og Kulturformidling, 2018)
Over the last 60 years, changes in librarianship have led to an increasing hybridization, and inspired a discussion on what a competence profile might look like for future library staff. Whether the structural changes were triggered by innovative processes, internationalization or by strengthening social and cultural capital, it resulted in altered self-image and fragmented forms of practice. We argue that shifting cultural policy regimes have intensified processes of hybridization and forced libraries to act as Gyro Gearlooses in a tirelessly search for new fields of activity, strategic alliances and more efficient working methods. Theoretically and methodically informed by neo-institutional theory and especially by historical institutionalism, we focus on the Janus-faced nature of change processes distinguishing 'preservation competences' from 'change competences' thus conceiving hybridization as a change with limitations or as constrained selection. After the analysis of cultural policy since the 1960s till the 1980s, we investigate hybridization based on a case study. Central to this are various models of international cooperation that reflect different experiences, competencies, and needs. The analysis shows that changes in the institutional framework are not necessarily the result of a deliberate strategy, but the random result of internal and external adaptations of libraries to their changing environments. In conclusion, we find that technical knowledge and the ability to maneuver in a project organization are not sufficient. This makes it even more important to develop an understanding of the permanently shifting power coalitions in organizational fields as a vehicle of institutional change processes.